Protection of Medical Record Data as a Form of Legal Protection of Health Data through the Personal Data Protection Act - Ni Putu Yuliana Kemalasari; I Putu Harry Suandana Putra (Catuspata, 2023)
This study aimed at analyzing government’s efforts to provide protection for medical record data of patients as a form of legal protection for patient’s medical data. In the midst of the flurry cases of personal data leakage by hackers, it has raised concerns from various parties about the possibility of medical records leaking of someone’s medical history. Medical history or medical record contains confidential information about a person’s condition related to health and the history of health care that has been carried out. It becomes particularly serious when it records certain diseases of the patient that should not be spread out to the public. In Indonesia, several regulations regarding the protection of personal data which is a person’s privacy rights have been formed. However, this is not enough to deal with the development of digital technology to provide legal certainty for the protection of personal data including medical records as one of the objectives of the law, namely to provide legal certainty and protection. Therefore, this study examines how the legal protection of medical record data based on legal protection according to positive law and the Personal Data Protection Act.